2020
DOI: 10.3390/cells10010016
|View full text |Cite
|
Sign up to set email alerts
|

Role of Notch Receptors in Hematologic Malignancies

Abstract: Notch receptors are single-pass transmembrane proteins that play a critical role in cell fate decisions and have been implicated in the regulation of many developmental processes. The human Notch family comprises of four receptors (Notch 1 to 4) and five ligands. Their signaling can regulate extremely basic cellular processes such as differentiation, proliferation and death. Notch is also involved in hematopoiesis and angiogenesis, and increasing evidence suggests that these genes are involved and frequently d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 163 publications
0
8
0
Order By: Relevance
“…KEGG pathway analysis showed that the highly expressed genes in cluster A with poor prognosis were mainly enriched in the Notch signaling pathway, while the lowly expressed genes were enriched in the TGF-β signaling pathway. Notch plays a role in promoting and maintaining lymphoid malignancies by regulating relevant signaling pathways ( 50 ). The Notch signaling pathway has been reported to be aberrantly activated in DLBCL ( 51 ), and it has also been found that Notch can interact with the tumor or stem cell microenvironment via stromal cells ( 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…KEGG pathway analysis showed that the highly expressed genes in cluster A with poor prognosis were mainly enriched in the Notch signaling pathway, while the lowly expressed genes were enriched in the TGF-β signaling pathway. Notch plays a role in promoting and maintaining lymphoid malignancies by regulating relevant signaling pathways ( 50 ). The Notch signaling pathway has been reported to be aberrantly activated in DLBCL ( 51 ), and it has also been found that Notch can interact with the tumor or stem cell microenvironment via stromal cells ( 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…There is accumulating evidence that Notch signaling plays a role in tuning the immune responses in tumors, which is in line with Notch signaling playing a pivotal role in normal hematopoiesis and in generation of various types of immune effector cells [ 94 ]. Notably, Notch signaling is a key regulator of the choice between the B- and T-cell lineages and subsequently regulates the specification of various T-cell subclasses [ 95 ]. Notch signaling also plays a role in inflammatory processes, for example by exacerbating the T-cell response in the experimental autoimmune encephalomyelitis (EAE) mouse model for multiple sclerosis [ 96 , 97 , 98 ].…”
Section: The Role Of Notch Signaling In the Tumor Microenvironmentmentioning
confidence: 99%
“…Later, its role in other hematological malignancies such as B-cell chronic lymphocytic leukemia (B-CLL) (Rosati et al, 2009), mantle cells lymphoma (MCL), Multiple Myeloma, AML, etc. has been well established (Gragnani et al, 2020). Recently, a genome-wide study in relapse cases of T-cell lymphoblastic lymphoma (T-LBL) identified Notch1 as the putative driver for relapse and malignancy (Khanam et al, 2020).…”
Section: Major Developmental Signaling In Cancer Notch Signalingmentioning
confidence: 99%